Optimal Design of Resource Element Mapping for Sparse Spreading Non-Orthogonal Multiple Access - Yu, Hanxiao; Fei, Zesong; Yang, Nan; Ye, Neng (IEEE wireless communications letters, 2018)
We propose a new design of the optimal resource element (RE) mapping patterns to maximize the sum-rate of a sparse spreading non-orthogonal multiple access system. In this system, the grouped users who use the same radio resource have different channel conditions. First, we formulate a sum-rate optimization problem subject to sparsity and power constraints. To solve this non-trivial optimization problem, we transform it to an equivalent penalized problem by deriving the closed-form penalty parameters. We then convert this problem to a sequence of subproblems using the difference of convex programming and propose an efficient algorithm to find the optimal solution. Numerical results demonstrate that the proposed algorithm achieves a higher sum-rate and a superior block error rate performance than the conventional RE mapping schemes.